Parameters of cloud to cloud and intra-cloud lightning strikes to CFC and metallic aircraft structures - Fisher, J.; Hoole, P.R.P; Pirapaharan, K.; Hoole, S.R.H. (IEEE, 2017)
This paper presents for the first time an assessment of the impact of direct cloud–to-cloud (CC) and intra-cloud (IC) lightning flash on a commercial and a military aircraft. In contrast to cloud-to-ground (CG) lightning strikes to aircraft, where measurements of CG flash measurements may be extended to aircraft strikes, CC and IC flashes are not so accessible. The effects of CC and IC flashes differ from CG flash largely owing to the earth resistance present in CG flashes which imposes limits on the lightning return stroke. It applies the experimentally-attested transmission line model which was reviewed in a previous companion paper to assess the impact on metallic and carbon fiber composite (CFC) structures of modern aircraft. It compares the electrical impact of CC lightning flash on aircraft made of CFC and metallic structures. The simulations and analysis of voltages and the first return stroke current waveforms demonstrate the important distinctions in the characteristics of direct CC lightning effects on metallic and non-metallic airframes. Among the significant results observed are large differences in current time derivatives on the surface of the carbon fiber composites and metallic airframes. Further observations show that there are rise times for the voltage and currents which fall within the subnano and submicro seconds yielding large time derivatives for both the voltages and the currents. This can have important implications for the shielding and protection of the aircraft electrical and electronics systems.